Sistem Monitoring Air Conditioner (AC) Pada Ruang Kelas Institut Teknologi Kalimantan Berbasis Internet of Things (IoT): Sistem Monitoring Air Conditioner (AC) Pada Ruang Kelas Institut Teknologi Kalimantan Berbasis Internet of Things (IoT) - Amalia Rizqi Utami; Barokatun Hasanah; Muhammad Iqbal Sep Firsen; Ryan Fikri (SPECTA Journal of Technology, 2026)
This research discusses the implementation of a monitoring system based on Internet of Things (IoT) technology to monitor air conditioning usage in the form of a website. This system is designed to collect data about air conditioner usage in real time and monitor the on/off conditions of the air conditioner. Several components are used such as the DHT11 module as a temperature sensor which functions to read room temperature, the PZEM- 004t module which functions to read voltage, current and power which operates on AC when it is off or on, the Arduino UNO microcontroller to process input/output data, ESP8266 for connecting to a wi-fi network. In addition, software is used to support the research process such as Arduino to program the Arduino UNO microcontroller, XAMPP to create a database, and Visual Studio Code to create programs on websites. In this study, there are several stages such as analysis of user needs, system design, system testing, data analysis, and conclusions. Then after testing and data collection, the current and power values were obtained when the AC was off, namely 0.4 A and 1.7 Watt – 1.8 Watt. When the AC is on, the current and power values are 1.08 A – 1.19 A and the power is 216.8 Watt – 244.6 Watt.